1995
DOI: 10.1249/00005768-199505000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Factors in daily physical activity related to calcaneal mineral density in men

Abstract: HUTCHINSON, T. M., R. T. WItALEN, T. M. CLEEK, J. M. VO-GEL, and S. B. ARNAUD. Factors in daily physical activity related to calcaneal mineral density in men. Med. Sci. Sports Exert., Vol. 27, No. 5, pp. 745-75(i, 1995. To determine the factors in daily physical activity that influence the mineral density of the calcaneus, we recorded walking steps and the type and duration of exercise in 43 healthy 26-to 51-yr-old men. Areal (g-cm 2) calcaneal bone mineral density (CBMD) was measured by single energy x-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Similarly, in young adult men, a higher lifetime OI was associated with increased bone circumference and cortical bone area (Nilsson et al, 2009). Hutchinson et al (1995) found that calcaneal BMD was related with reported minutes of high load exercises, but not with daily number of steps. The present study using objective continuous accelerometric measurements enabled quantification of all daily loadings to give more detailed information on the osteogenic response of daily activities.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, in young adult men, a higher lifetime OI was associated with increased bone circumference and cortical bone area (Nilsson et al, 2009). Hutchinson et al (1995) found that calcaneal BMD was related with reported minutes of high load exercises, but not with daily number of steps. The present study using objective continuous accelerometric measurements enabled quantification of all daily loadings to give more detailed information on the osteogenic response of daily activities.…”
Section: Discussionmentioning
confidence: 92%
“…An increase of 5 points on the activity score is equivalent to, for example, going for a walk or cycling for 2.5 h per week. Several intervention studies in elderly people have shown that especially weightbearing activities, leading to high strains in the skeleton, may be beneficial to maintain bone mass [17,26,27], but other studies were unable to demonstrate such an effect of physical activity on bone mass [28,29]. Although these results suggest a protective effect of daily physical activity for skeletal integrity, physical activity in this very elderly population may be an indication of the level of physical activity in the past.…”
Section: Discussionmentioning
confidence: 74%
“…Our data showed sex did not modify the relationship between steps and hip aBMD, thus the positive effect of steps was the same in males and females. Two previous studies looking at men found that regular aerobic exercise [21] and walking [22] had no measurable effect on bone mass. The contradictory findings between our and the aforementioned studies may relate to the age of participants.…”
Section: Discussionmentioning
confidence: 88%
“…The majority of research on walking, and even to an extent, physical activity and bone mass has been done in postmenopausal women. The limited studies in men showed regular aerobic exercise [21] or walking [22] had no measurable effect on BMD.…”
Section: Introductionmentioning
confidence: 95%